A MATLAB GUI program for reservoir management to simultaneously optimise sediment release and power generation. (15th October 2022) - Li, Fang-Fang; Wang, Hong-Ru; Qiu, Jun
Abstract: Sedimentation affects the normal function of reservoirs and is a decisive factor in the reservoir's service life. Flushing sediment during reservoir operation is an effective non-engineering measure to alleviate reservoir sedimentation; however, lowering water level to discharge more flow conflicts with hydropower generation. In this study, reservoir management software is developed to simultaneously optimise sediment discharge and hydropower generation with the reservoir discharge as the decision variables. The sediment transport rate is calculated by an integral of the vertical distribution of suspended load concentration and flow velocity instead of empirical formulas. The model is solved by the most widely used multi-objective optimisation algorithm NSGA-II, resulting in the optimal schedule corresponding to the maximal sediment discharge and hydropower generation, which can be displayed graphically in the software. The software was developed in MATLAB with a Graphical User Interface (GUI) and applied to a large reservoir and can be generalised to other reservoirs. The results show that within the recommended discharge variation of 5%, the sediment release can be increased by 2.07 × 10 6  t as a reduction of per 10 10  kW h in annual power generation. Compared with the original scheme, sediment release can be increased most by 3.31% at the cost of 0.03% loss of power generation. Moreover, the dual objective in the flood season was optimised by 7.30% and 3.92%, respectively. Highlights: Novel calculation equation sediment transport rate for reservoirs based on vertical distribution of suspended load. Multi-objective reservoir operation for sediment flushing and power generation. Common Software Platform providing optimal reservoir schedule for decision makers.